Assessing Waterborne Disease Vulnerabilities in the Blocks of Kalahandi District of Odisha, India - Martand Mani Mishra; Netrananda Sahu (Wolters Kluwer Medknow Publications, 2022)
Background: Outbreaks of waterborne diseases caused by the contamination of water in the rural and tribal regions have become an area of prime concern in the research arena. The impact and intensity of waterborne diseases are expected to increase in these socioeconomic backward regions. Objective: The purpose of the study is to calculate the waterborne disease vulnerability index (DVI) for 13 blocks of the Kalahandi district of Odisha. Diarrhea and typhoid are two major diseases prevailing in each block of the district. Materials and Methods: Livelihood vulnerability index has been applied with some modifications to calculate the DVI for each block. In the DVI calculation, diseases are taken as an indicator for the exposure section. The sensitivity and adaptive capacity sections are categorized into two subcomponents to study the vulnerability of each block. Results: We have observed uneven distribution of diarrhea and typhoid among the blocks of Kalahandi. The result indicates that vulnerable populations and infrastructure play an important role in enhancing vulnerability whereas educational and health-care capacity reduces its impact. We have found that more than 50% of blocks in the district are categorized in moderate to high vulnerable zones. Conclusion: This study is done to understand the relationship between disease exposure, related vulnerability, and adaptive capacity. It is unique in the way the indicators have been chosen in the proposed method for the calculation of DVI and will have a higher degree of practical applicability.